EVALUASI SEDIAAN MASKER GEL PEEL OFF EKSTRAK LIDAH BUAYA DENGAN BASIS POLIVYNIL ALKOHOL: EVALUASI SEDIAAN MASKER GEL PEEL OFF EKSTRAK LIDAH BUAYA DENGAN BASIS POLIVYNIL ALKOHOL - Marlina Indriastuti (LPPM STIKes Muhammadiyah Ciamis, 2020)
Aloe vera is a potential natural ingredient that can be used as a cosmetic ingredient because it has antioxidant properties and nutrients that are good for the skin. The purpose of this study was to determine the effect of differences in PVA concentrations as a basis for evaluating peel off gel mask preparations.The type of research to be carried out is experimental research. The sample that will be used is the extract of aloe vera meat (aloe vera). The peel off mask formulation from aloe vera extract was made from 3 formulas with different concentrations of PVA, namely 10%, 15%, and 20%. After that, a physical evaluation of the gel exfoliating mask preparation was carried out which included the organoleptic test, viscosity, pH test, spreadability, and drying time. The evaluation data will be analyzed statistically using one way analysis of variance (ANOVA). The results showed that differences in the concentration of PVA in each formula could affect the viscosity value and the drying time of the preparation. It can be concluded that the formula that meets the standards is formula I with a concentration of 10%.